Review of The Ryukyu Islands: A New History from the Stone Age to the Present by Gregory Smits. Chicago: The University of Chicago Press, 2025. 488 pages. - Laubenstein, Victor; Huerta Nunes, Sofia (Silva Iaponicarum, 2026)
Review of The Ryukyu Islands: A New History from the Stone Age to the Present by Gregory Smits. Chicago: The University of Chicago Press, 2025. 488 pages.